The Influence of Personal Selling and E-Marketing Marketing Communications of Dapurnya Ami UMKM on Consumer Brand Awareness in Banuhampu District, Agam Regency - Shafira Triana putri; Mazdalifah; Dewi Kurniawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the impact of marketing communication through personal selling on consumer brand awareness in Banuhampu District, Agam Regency. Additionally, this study evaluates the effect of electronic marketing communication (e-marketing) by the micro, small, and medium enterprises (MSME) Dapurnya Ami on consumer brand awareness in the area. The research method used is a quantitative approach conducted in Banuhampu District, which consists of seven villages. The sample was selected using proportionate stratified random sampling, purposive sampling, and accidental sampling techniques, with a total of 400 respondents. Data was collected through questionnaires distributed to consumers who are the target market of the MSME Dapurnya Ami. Data analysis was performed using various techniques, including single table analysis, cross-tabulation analysis, and hypothesis testing using Spearman's rho rank. The results show a positive correlation between the personal selling marketing communication of Dapurnya Ami and consumer brand awareness, indicated by r=0.001 and p=0.718. This suggests that the first hypothesis is accepted with a significance level of less than 0.05. Furthermore, the correlation between electronic marketing communication (e-marketing) of Dapurnya Ami and consumer brand awareness is also positive, with r=0.001 and p=0.836, indicating that the second hypothesis is accepted at the same significance level